Glycated haemoglobin A1c for diagnosing diabetes in Chinese population: cross sectional epidemiological survey. (17th May 2010) - Bao, Yuqian; Ma, Xiaojing; Li, Huating; Zhou, Mi; Hu, Cheng; Wu, Haiya; Tang, Junling; Hou, Xuhong; Xiang, Kunsan; Jia, Weiping
Abstract : Objectives To evaluate haemoglobin A1c (HbA1c ) in diagnosing diabetes and identify the optimal HbA1c threshold to be used in Chinese adults. Design Multistage stratified cross sectional epidemiological survey. Setting Shanghai, China, 2007-8. Participants 4886 Chinese adults over 20 years of age with no history of diabetes. Main outcome measures Performance of HbA1c at increasing thresholds for diagnosing diabetes. Results The area under the receiver operating characteristics curve for detecting undiagnosed diabetes was 0.856 (95% confidence interval 0.828 to 0.883) for HbA1c alone and 0.920 (0.900 to 0.941) for fasting plasma glucose alone. Very high specificity (96.1%, 95% confidence interval 95.5% to 96.7%) was achieved at an HbA1c threshold of 6.3% (2 SD above the normal mean). Moreover, the corresponding sensitivity was 62.8% (57.1% to 68.3%), which was equivalent to that of a fasting plasma glucose threshold of 7.0 mmol/l (57.5%, 51.7% to 63.1%) in detecting undiagnosed diabetes. In participants at high risk of diabetes, the HbA1c threshold of 6.3% showed significantly higher sensitivity (66.9%, 61.0% to 72.5%) than both fasting plasma glucose ≥7.0 mmol/l (54.4%, 48.3% to 60.4%) and HbA1c ≥6.5% (53.7%, 47.6% to 59.7%) (P<0.01). Conclusions An HbA1c threshold of 6.3% was highly specific for detecting undiagnosed diabetes in Chinese adults and had sensitivity similar to that of using a fasting plasma glucose threshold of 7.0 mmol/l. This optimal HbA1c threshold may be suitable as a diagnostic criterion for diabetes in Chinese adults when fasting plasma glucose and oral glucose tolerance tests are not available.